2021
DOI: 10.1111/age.13117
|View full text |Cite
|
Sign up to set email alerts
|

Improving the resolution of canine genome‐wide association studies using genotype imputation: A study of two breeds

Abstract: Summary Genotype imputation using a reference panel that combines high‐density array data and publicly available whole genome sequence consortium variant data is potentially a cost‐effective method to increase the density of extant lower‐density array datasets. In this study, three datasets (two Border Collie; one Italian Spinone) generated using a legacy array (Illumina CanineHD, 173 662 SNPs) were utilised to assess the feasibility and accuracy of this approach and to gather additional evidence for the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Genotype imputation of WGS variants was employed on the 82 unrelated Bearded Collies included in the previous GWAS in an effort to refine the list of variants for further exploration. Imputation accuracy, estimated as the percentage of correctly imputed genotypes in 24 Bearded Collies, averaged 91.7% for SNPs (range 81.3-98.3%) and 87.6% for insertions or deletions (i.e., indels; range 78.5-97.8%) on CFA12, and 86.8% for SNPs (range 75.1-99.4%) and 84.6% for indels (range 73.0-98.9%) on CFA17, similar to what has previously been achieved with a multi-breed reference panel [16][17][18].…”
Section: Variants From Imputed Datasetsupporting
confidence: 81%
See 1 more Smart Citation
“…Genotype imputation of WGS variants was employed on the 82 unrelated Bearded Collies included in the previous GWAS in an effort to refine the list of variants for further exploration. Imputation accuracy, estimated as the percentage of correctly imputed genotypes in 24 Bearded Collies, averaged 91.7% for SNPs (range 81.3-98.3%) and 87.6% for insertions or deletions (i.e., indels; range 78.5-97.8%) on CFA12, and 86.8% for SNPs (range 75.1-99.4%) and 84.6% for indels (range 73.0-98.9%) on CFA17, similar to what has previously been achieved with a multi-breed reference panel [16][17][18].…”
Section: Variants From Imputed Datasetsupporting
confidence: 81%
“…The purpose of this study was to explore whole genome sequencing (WGS) data from SLO-affected and healthy Bearded Collies in order to identify putative causative variants within the two GWAS-associated regions on CFA12 and CFA17. To refine the large number of WGS variants observed in the regions of interest, genotype imputation, which has been shown to accurately predict WGS genotypes based on data from high-density SNP arrays [16][17][18], was also employed.…”
Section: Introductionmentioning
confidence: 99%
“…While this study suggested discarding sites with a MAF < 0.05, our data argues for selecting variants with imputation quality > 0.90 and reference MAFs > 1%. This reflects both the large number of dogs and breeds as well as the variation captured in village dogs in our dataset, both of which are critical for the development of any reference panel, in dogs [ 119 , 120 ] or otherwise [ 121 ]. For the Illumina CanineHD BeadChip platform, the criteria we propose will provide imputed genotypes with NRC rates > 0.85 for over 8 M sites, whereas for the low-pass WGS and Axiom Canine HD Array platforms, these criteria provide NRC rates of approximately 0.95 for over 10 M sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, species with reference panels lacking ancestral diversity show reduced accuracy (e.g., pigs) (Erven et al 2022). Imputation of modern dogs has shown promising results as a method to increase SNP density (Hayward et al 2016, 2019; Jenkins et al 2021; Buckley et al 2022; Morrill et al 2022; Meadows et al 2023), but the accuracy of imputation has not been previously investigated for ancient canids, nor have results from such been applied to questions of canine migration or domestication.…”
Section: Introductionmentioning
confidence: 99%